2018
DOI: 10.1021/acs.jpclett.8b02442
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Molecular Assembly via Dynamic Confinement of Solvent

Abstract: Assembly from ultrasmall solution droplets follows a different dynamic from that of larger scales. Using an independently controlled microfluidic probe in an atomic force microscope, subfemtoliter aqueous droplets containing polymers produce well-defined features with dimensions as small as tens of nanometers. The initial shape of the droplet and the concentration of solute within the droplet play significant roles in the final assembly of polymers due to the ultrafast evaporation rate and spatial confinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 54 publications
(83 reference statements)
2
31
0
Order By: Relevance
“…The concept of controlled assembly using small liquid droplets was first reported by our team using macromolecules (e.g., star polymers). 13 This result extends the concept to a much smaller molecule, PEG-bisTz, which has a hydrodynamic radius of 1.5 nm.…”
Section: Controlled Assembly Of Peg-bistz In Individual Ultrasmall Dropletssupporting
confidence: 60%
See 4 more Smart Citations
“…The concept of controlled assembly using small liquid droplets was first reported by our team using macromolecules (e.g., star polymers). 13 This result extends the concept to a much smaller molecule, PEG-bisTz, which has a hydrodynamic radius of 1.5 nm.…”
Section: Controlled Assembly Of Peg-bistz In Individual Ultrasmall Dropletssupporting
confidence: 60%
“…This setup enabled delivery of aqueous droplets as small as 0.4 attoliter (aL). 13 First, we demonstrated that the geometry and size of the individual and concrete assemblies can be controlled with PEG-bisTz molecules tightly packed within. Under a contact force of 40 nN, delivery pressure of 200 mbar, and contact time of 0.2 s, 250 aL droplets of PEG-bisTz solution were delivered on the AAPTMS SAM surfaces, as shown in Figure 2a.…”
Section: Controlled Assembly Of Peg-bistz In Individual Ultrasmall Dropletsmentioning
confidence: 99%
See 3 more Smart Citations